Ambient Coarse Particulate Matter and Hospital Admissions for Ischemic Stroke: A National Analysis. Issue 4 (April 2019) - Tian, Yaohua; Liu, Hui; Xiang, Xiao; Zhao, Zuolin; Juan, Juan; Li, Man; Song, Jing; Cao, Yaying; Wu, Yao; Wang, Xiaowen; Chen, Libo; Wei, Chen; et al.
Abstract : Background and Purpose—: Evidence on the effects of coarse particulate matter (PM10–2.5 ) on ischemic stroke is limited and inconsistent. We evaluated the acute effects of PM10–2.5 exposure on hospital admissions for ischemic stroke in China. Methods—: We conducted a national time-series analysis of associations between daily PM10–2.5 concentrations and daily hospital admissions for ischemic stroke in China between January 2014 and December 2016. Hospital admissions for ischemic stroke were identified from the database of Urban Employee Basic Medical Insurance, which contains data from 0.28 billion beneficiaries. We applied a city-specific Poisson regression to examine the associations of PM10–2.5 and daily ischemic stroke admissions. We combined the city-specific effect estimates with a random effects meta-analysis, and further evaluated the exposure-response relationship curve and potential effect modifiers. Results—: We identified >2 million hospital admissions for ischemic stroke in 172 Chinese cities. A 10 μg/m 3 increase in PM10–2.5 concentrations (lag day 0) was associated with a 0.91% (95% CI, 0.73–1.10) increase in hospital admissions for ischemic stroke. The association remained significant after adjusting for PM2.5 (percentage change, 0.96%; 95% CI, 0.75–1.18). The exposure-response relationship was approximately linear, with a moderate response at lower levels (<200 μg/m 3 ) and a steeper response at higher levels. The association was stronger in cities with lower PM10–2.5 concentrations, higher temperatures, or higher relative humidity. Conclusions—: This nationwide study provides robust evidence of the short-term association between exposure to PM10–2.5 and increased hospital admissions for ischemic stroke and supports the hypothesis that the association differs by city characteristics. Abstract : Supplemental Digital Content is available in the text.